Polityka pieniężna u progu XXI wieku. Ekspozycja problemu - Hetmańczuk, Adam (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The author makes an introduction to an interesting discussion about globalization problems. This article takes up a very important topic of the relationship between monetary policy and process of internationalizing business activity. The ongoing global economic integration influences the conduct of monetary policy through its powerful effects on the economic environment, in which monetary policy must effectively work. Globalization adds a new dimension of complexity to the analysis of financial conditions and their determinants, which monetary policy makers must take into account. Through its influence on financial markets, globalization may have affected the operation of central bank policy by changing the relative importance of the various factors that determine the domestic inflation rate. The short analysis carried out in this paper highlights a globalization as a threat to the effectiveness of inflation stabilizing action undertaken by monetary authority. The author tries to answer the question how globalization will influence the monetary policy making in the near future. Under globalization conditions monetary policy reactions to the external shocks may be wrong and harmful. The unexpected changes in the global economy may result in sudden growth of the domestic prices, may have far-reaching negative consequence for economy. In the author's opinion, it needs further discussion on this issue in the context of central bank policy and its responsibility for a low and stable level of domestic inflation. More research on the effectiveness of monetary policy in the age of globalization would be very useful. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 141-153